The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/neuros/nyx238
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Intracranial Aneurysm Rupture: A Systematic Review

Abstract: BACKGROUND Intracranial aneurysm rupture prediction is poor, with only a few risk factors for rupture identified and used in clinical practice. OBJECTIVE To provide an overview of all the risk factors (including genetic, molecular, morphological, and hemodynamic factors) that have potential for use in clinical practice. METHODS We systematically searched PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 29 publications
2
66
0
Order By: Relevance
“…In contrast, a larger aneurysm size is commonly related to an increased rupture risk [14,17], which is conflicting with the negative association with aneurysm width in our model. However, some research indicates that the ratio between aneurysm and parent vessel size is a better discriminant between ruptured and unruptured aneurysms [12]. Moreover, aneurysm width did not differ significantly between ruptured and unruptured aneurysms in our univariate comparison.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In contrast, a larger aneurysm size is commonly related to an increased rupture risk [14,17], which is conflicting with the negative association with aneurysm width in our model. However, some research indicates that the ratio between aneurysm and parent vessel size is a better discriminant between ruptured and unruptured aneurysms [12]. Moreover, aneurysm width did not differ significantly between ruptured and unruptured aneurysms in our univariate comparison.…”
Section: Discussionmentioning
confidence: 52%
“…It is known that hemodynamics play an important role in the aneurysm pathogenesis [10]. Hemodynamics in turn are influenced by aneurysm geometry, and several morphological parameters have been related to aneurysm rupture [11, 12]. Further risk factors include aneurysm location, symptoms caused by the aneurysm, as well as the patient’s age and smoking and hypertension status [7, 1316].…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators found strong correlations between greater SR and rupture status. 61,68 In their systematic review and meta-analysis, Kleinloog et al 33 identified irregular aneurysm shape, larger AR, larger SR, higher bottleneck factor (aneurysm width divided by the diameter of the neck), and aneurysm height-to-width ratio as morphological characteristics with strong levels of evidence for increased risk of rupture. Morphological characteristics with moderate levels of evidence for association with rupture included downward/inferior direction of the dome and volume-toostium ratio (ratio of the aneurysm volume to the area of the neck).…”
mentioning
confidence: 99%
“…12,17,23 The pathophysiological mechanisms leading to aneurysm rupture are not yet fully understood; however, a plethora of risk factors have been suggested in the literature. 13 These risk factors include patient-related variables such as sex or smoking status, genetics, geometric factors describing the shape of an IA, and hemodynamic factors. Hemodynamics are believed to play an important role in aneurysm development, growth, and rupture through biomechanical signaling processes in the vessel wall.…”
mentioning
confidence: 99%